Organizations, projects and culture - van Cleeff, Jules; van Nispen, Pieter (Organizacje, projekty i kultura, 2016)
Purpose: to explore and demonstrate the effects of organizational culture on projects; in particular project culture and project management style. Methodology/approach: descriptive and explorative; through students’ groups. Findings: the cultural relationship between organizations; their projects and the third parties involved (clients) has quite some impact and is more complicated than expected. Implications/limitations: need for more detailed and structured research; including operationalization of concepts. Originality/ value: although some attention has been paid to the topic; more research is required to demonstrate the impact of culture on the realisation and effectiveness of internal and external projects
Management Forum, 2016, vol. 4, no. 3, s. 16-22
Keywords: organization; organizational culture; projects; project culture; project management; organizacja; kultura organizacyjna; projekty; kultura projektu; zarządzanie projektem